Juvenile and adult mortality patterns in a vicuña (Vicugna vicugna) population - Donadio, Emiliano (2012)
Neotropical ungulates are poorly understood with regard to age-specific mortality and how it relates to different mortality causes. During January 2008–April 2011, we investigated mortality patterns of calf (¨<1 year old) and adult vicunas (Vicugna vicugna) in west-central Argentina. Specifically, we analyzed whether birth mass, birth date, and sex of radiomarked vicuna calves affected 1st-year survival; quantified cause of death for marked calves and unmarked adults; and explored how primary productivity and quality of forage and diet related to body condition of adult vicuna carcasses. Birth mass was a strong predictor of 1st-year survival: a 1-kg (~18%) increase in birth mass resulted in a 54% decline in the risk of death. Further, low survival rate in 1 calendar year was associated with low mean birth mass during that year, but not with population density and forage quality in the previous year. Puma (Puma concolor) predation accounted for > 49% (n=93) and 91% (n=89) of the mortality in calves and adults, respectively. Body condition of adult vicunas killed by pumas varied seasonally and correlated with seasonal changes in primary productivity and forage and diet quality. Our results highlighted the importance of puma predation and low birth mass as proximate causes of vicuna mortality. How environmental factors (e.g., early summer precipitation) influence forage and ultimately mortality has yet to be determined.